Differences in Adolescent Experiences of Polyvictimization and Suicide Risk by Sexual Minority Status. (24th November 2020) - Johns, Michelle M.; Lowry, Richard; Hipp, Tracy N.; Robin, Leah; Shafir, Shira
Abstract : Sexual minority adolescents (SMA) report more suicide risk behaviors than heterosexual adolescents. Polyvictimization (co‐occurrence of multiple types of victimization) may be an important, underresearched correlate of this disparity. With the 2017 national Youth Risk Behavior Survey ( N  = 13, 179), national estimates of polyvictimization and suicide risk were assessed among high school students by sexual minority status (SM vs. heterosexual), and multivariate relationships between sexual minority status, polyvictimization, and suicide risk were tested. Additionally, risk profiles of those who experienced polyvictimization (2 + types of victimization; n  = 1, 932) were compared across sexual minority status. Results confirm that SMA are more likely to experience polyvictimization than heterosexual adolescents (31.8% v. 12.9%, respectively); however, also indicate that polyvictimization does not fully explain elevated suicide risk among SMA.